Mapping Properties For Conic Regions Associated With Miller Ross Function - Sabihee Anwaar; Muhammad Amin; Saima Mushtaq; Zunera Shoukat, (Dialogue Social Science Review (DSSR), 2025)
In this paper, our primary objective is to determine sufficient conditions under which the convolution operator belongs to the classes and .